Actual Gear Surface Static Unloaded Transmission Error of Spiral Bevel Gear and Its Effect on Dynamic Characteristic - Zhisheng Chen; Siyu Chen; Jinyuan Tang; Shandong Peng (Jixie chuandong)
Taking a pair of spiral bevel gear pairs as the research object, a static unloaded transmission error model of actual tooth surface is established, which is free from tooth surface equation. The model is based on the tooth surface point measured by the coordinate measuring instrument，the model forms a discrete tooth surface point through interpolation and obtains the static unloaded transmission error through contact analysis. The theoretical tooth surface STE of the model is compared with the theoretical tooth surface STE obtained by the classic TCA, the correctness of the method is verified, and the actual tooth surface STE is calculated. The three-dimensional coupling dynamics model of spiral bevel gear pair is established. In this dynamics model, factors such as rotor, load, time-varying meshing stiffness and backlash are considered. The STE of theoretical tooth surface and actual tooth surface are introduced into the dynamics model in the form of discrete points, and their influence on the dynamics performance of spiral bevel gear pair is compared.